Isocyanate adhesive composition, formaldehyde-free artificial board and preparation method of formaldehyde-free artificial board
By using multifunctional isocyanate and aqueous emulsion in the surface and core layer of the artificial-free artificial board for hot compression preparation, the problems of hygroscopic expansion and expansion of the artificial-free artificial board are solved, and its waterproof performance is significantly improved, satisfying the Environmental protection and cost requirements achieve super waterproof performance.
Patent Information
- Application Number
- CN202411450128.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Morphalene-free artificial boards are prone to hygroscopic expansion and expansion during use, resulting in poor waterproofing performance and cannot meet environmental protection and cost requirements.
Using an isocyanate adhesive composition, including a multifunctional isocyanate, an aqueous emulsion and a sulfonamide additive, the preparatively free artificial board is prepared by applying the composition to the surface and core layer for thermal compression, thereby improving the waterproof performance of the board. .
It significantly improves the water resistance of legacy-free artificial boards, reduces the problem of raising scales, meets environmental protection and cost requirements, and achieves super waterproof performance through testing.
Abstract
Description
Technical Field
[0001] The invention relates to the field of formaldehyde-free artificial boards, and in particular to an isocyanate adhesive composition that improves the water resistance of formaldehyde-free artificial boards and improves the problem of the expansion of the formaldehyde-free boards, and a method for preparing the formaldehyde-free artificial boards. Background Art
[0002] Wood or other non-wood plants are used as raw materials, separated into particles, needle-shaped or flaky shavings, fibers and other units through mechanical processing, and then adhesives or other additives are applied and hot-compressed to make artificial boards, which have quickly gained market recognition for their high cost-effectiveness. Traditional artificial board production is mainly based on "trialdehyde glue", including urea-formaldehyde resin adhesive, phenolic resin adhesive and melamine urea-formaldehyde resin adhesive. These adhesives will release formaldehyde gas during manufacturing, use and finished board products, polluting the environment and endangering human health.
[0003] PMDI (polymethylene polyphenyl isocyanate) adhesive can solve the problem of formaldehyde release. Since PMDI itself does not contain formaldehyde, there is no artificial formaldehyde release in the finished board, which is green and environmentally friendly. PMDI is used as an adhesive to prepare artificial boards. The reaction mechanism is that the functional group -NCO in PMDI reacts with water in wood or non-wood plant raw materials under hot pressing and high temperature to produce products such as urea (-NH-CO-NH-) and biuret (-NH-CO-N-CO-NH-), which bind with the raw material units to form artificial boards that meet national standards. No harmful substances are produced during the entire reaction process. Another advantage of PMDI as an adhesive to prepare artificial boards is that the amount added is small. The amount used in each cubic board is about 10-40 kilograms, which is much lower than the amount used in urea-formaldehyde resin. With the upgrading of technology and the improvement of equipment performance, the amount of PMDI adhesive is being continuously optimized, and the amount added is getting lower and lower.
[0004] The formaldehyde-free artificial boards prepared with ultra-low PMDI adhesive addition will introduce a more obvious problem - poor wrapping of wood units. Since wood is a hygroscopic material, the finished boards will absorb moisture and expand during later use, eventually causing size expansion and deformation, which is not desired by artificial board manufacturers and downstream furniture companies.
[0005] Particleboard has become the main type of board for custom furniture due to its advantages such as easy processing, low price and stable size. Patent CN218140367U discloses a high-strength waterproof and environmentally friendly particleboard, which uses an adsorption layer and a waterproof layer placed on the surface of the particleboard substrate to achieve this. The preparation process is complex and the cost is high, and the edges will also absorb moisture and expand. Patent CN117464797A discloses a process method for improving the moisture resistance of particleboard. The raw material used in this patent is pine wood. The moisture resistance is improved by adding moisture-proof agents and adjusting the process. However, the source of raw materials for all-pine wood boards is limited. Artificial board companies mainly use eucalyptus and miscellaneous wood, and large-scale applications are limited. Patent CN219479601U discloses a waterproof composite cabinet board, including an inner waterproof board, a spacer and a flexible soft board. The overall processing technology is complex and the cost is high, and the waterproof problem of the board is not fundamentally solved. In the papers published by Yang Jiayi, "Research on Adding Waterproofing Agents to Urea-Formaldehyde Resin Adhesives", and Gou Zhili, "A Brief Discussion on Methods for Improving the Water Absorption and Thickness Expansion Rate of Particleboard", paraffin emulsion is added as a waterproofing agent to reduce the moisture absorption and thickness expansion rate of particleboard. However, the environmental performance of the board cannot meet the formaldehyde-free requirements, and increasing the amount of paraffin added will lead to increased glue consumption and increased production costs. As time goes by, the moisture-proof performance of the board still cannot meet the requirements.
[0006] Therefore, an adhesive composition is needed to improve the waterproof and moisture-proof properties of formaldehyde-free artificial boards, improve the water resistance of formaldehyde-free artificial boards, and improve the size expansion problem of formaldehyde-free boards. Summary of the invention
[0007] The purpose of the present invention is to provide an adhesive composition and a method for preparing a formaldehyde-free artificial board using the composition to improve the problem of formaldehyde-free artificial board having poor moisture resistance and easy expansion in size, in order to solve the problem of formaldehyde-free artificial board having poor moisture resistance and easy expansion in size.
[0008] To solve the above problems, the present invention provides the following technical solutions:
[0009] An isocyanate adhesive composition capable of improving the water resistance of formaldehyde-free artificial panels comprises the following components:
[0010] (a) 100 parts by mass of polyfunctional isocyanate;
[0011] (b) 3-50 parts by mass, preferably 15-30 parts by mass, of an aqueous emulsion;
[0012] (c) Sulfonamide auxiliary agent: 1-20 parts by weight, preferably 1-5 parts by weight.
[0013] The component (a) of the present invention is a multifunctional isocyanate selected from the following four categories: aromatic polyisocyanates, aliphatic polyisocyanates, aromatic aliphatic polyisocyanates and alicyclic polyisocyanates. The use of any one of the above four categories or a combination of multifunctional isocyanates is within the scope of the present invention. Relatively low-priced aromatic isocyanates are the preferred adhesives, including toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) and polymeric diphenylmethane diisocyanate (polymeric MDI or PMDI);
[0014] Preferably, the multifunctional isocyanate is PMDI. More preferably, PMDI has an average molecular weight of 320-420, an average functionality of 2.5-3.0, and a viscosity of about 150-250 cP at 25°C.
[0015] The component (b) of the present invention is an aqueous emulsion, which may be one or more of aqueous polyurethane emulsion (PUD), aqueous acrylic emulsion (PA), ethylene-vinyl acetate emulsion (EVA), polyvinyl acetate emulsion (PVAc), polyvinyl alcohol emulsion (PVA), preferably EVA emulsion;
[0016] The aqueous polyurethane emulsion preferably has a solid content of 45%-55%, and its preparation raw materials include isocyanate, polyol, and hydrophilic compound. The isocyanate may be an aromatic diisocyanate and / or an aliphatic diisocyanate, the polyol may be a polyether polyol, a polyester polyol, or a polyether polyester mixed polyol, and the hydrophilic compound may be a sulfonic acid hydrophilic compound and / or a carboxylic acid hydrophilic compound;
[0017] The ethylene-vinyl acetate emulsion preferably has a solid content of 45%-55% and a viscosity of 600-1500 cP;
[0018] The aqueous acrylic emulsion is a milky white or nearly transparent viscous liquid, and its solid content is preferably 35%-45% and its viscosity is 800-1200cp. The preparation of acrylic emulsion requires raw materials such as acrylic acid, polyvinyl alcohol, and surfactant;
[0019] The polyvinyl acetate is a water-soluble adhesive, which is obtained by polymerization of vinyl acetate monomer under the action of an initiator, and the solid content is usually selected to be 40%-50%;
[0020] The polyvinyl alcohol emulsion is a high-viscosity aqueous solution prepared from instant polyvinyl alcohol. Preferably, the particle size is 100-150 mesh, the solid content is 5%-10%, and the viscosity range is 200-2000cp;
[0021] The water-based emulsion can increase the initial viscosity of the slab to enhance the formability of the board and facilitate continuous production.
[0022] The component (c) of the present invention is a sulfonamide auxiliary agent, selected from one or more of sulfamide, methoxybenzenesulfonamide, p-toluenesulfonamide, chlorosulfonamide, arylsulfonamide, p-aminobenzenesulfonamide, preferably p-aminobenzenesulfonamide; the purity is preferably above 99%, and the particle size is preferably 150-200 mesh;
[0023] The present invention can select one or more combinations of the above sulfonamide additives, and the amount is 1-20 parts by mass based on 100 parts by mass of component (a), preferably 1-5 parts by mass. Sulfonamide substances can promote the penetration of PMDI into wooden units and improve the waterproof performance of wood.
[0024] The present invention also relates to the use of the isocyanate adhesive composition in the preparation of artificial boards. The adhesive composition is used in the preparation of surface units of artificial boards.
[0025] A method for preparing an artificial board comprises the following steps:
[0026] (1): applying component (a), component (b) and component (c) to a surface layer raw material to prepare a surface layer unit;
[0027] Adding isocyanate to the core layer raw material to prepare a core layer unit;
[0028] (2): adjusting the moisture content of the surface layer unit and the core layer unit obtained in step (1), and then performing paving, pre-pressing, hot pressing and other processes to obtain a formaldehyde-free artificial board rough board;
[0029] (3): Cooling the rough board obtained in step (2) and performing sanding treatment to obtain a plain board;
[0030] (4): Sampling and testing the plain board obtained in step (3) according to GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels";
[0031] Wherein, in step (1), during the preparation of the surface layer unit, the aforementioned composition (i.e., (a) 100 parts by weight of a multifunctional isocyanate; (b) 3-50 parts by weight of an aqueous emulsion; and (c) 1-20 parts by weight of a sulfonamide auxiliary agent) is used, and the amount of component (a) is 2 wt% to 10 wt% of the mass of the surface layer raw material, preferably 3 wt% to 3.5 wt%;
[0032] In the preparation process of the core layer unit, the isocyanate is selected from aromatic polyisocyanates, aliphatic polyisocyanates, aromatic aliphatic polyisocyanates and alicyclic polyisocyanates, preferably toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) and polymeric diphenylmethane diisocyanate (polymeric MDI or PMDI), and more preferably PMDI. More preferably, the average molecular weight of PMDI is 320-420, the average functionality is 2.5-3.0, and the viscosity is about 150-250 cP at 25°C; the amount of isocyanate used is 2wt% to 10wt% of the core layer raw material, preferably 3wt% to 3.5wt%;
[0033] The surface layer and core layer raw materials can be wood crushed materials, bamboo crushed materials, straw crushed materials, cotton and linen stalk raw materials, etc., and the moisture content is preferably 2-6%; among them, preferably, the moisture content of the surface layer raw material is 3%-5%, and the moisture content of the core layer raw material is 2%-4%.
[0034] In step (2), the moisture content of the surface layer unit is adjusted to 13wt%-15wt%, and the moisture content of the core layer unit is adjusted to 4wt%-6wt%.
[0035] Paving refers to the uniform paving of the artificial board units with glue and additives into a three-layer structure of surface-core-surface, with a paving quality ratio of 1-1.2:2.6-3:1-1.2. Pre-pressing refers to the use of pre-pressing equipment to shape the slab, with a pre-pressing thickness of 50-55mm. Hot pressing generally uses hot pressing equipment with a temperature of 210-230℃ to hot press the slab to cure the glue and form the board, and the hot pressing time is 100-150s.
[0036] The beneficial effects of the present invention are:
[0037] The particleboard prepared by the composition can significantly improve water resistance and reduce the problem of furniture expansion during long-term use. DETAILED DESCRIPTION
[0038] The embodiments of the present invention are further described below in conjunction with examples, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0039] Polymethylene polyphenyl isocyanate glue (PMDI): functionality about 2.7, viscosity 180-250 cP at 25°C, -NCO content 30.5-32%, Wanhua Chemical Group Co., Ltd.;
[0040] Ethylene vinyl acetate emulsion (EVA): 102H, white emulsion, solid content ≥52%, viscosity: 1000-1200cP;
[0041] p-Aminobenzenesulfonamide: high-grade pure GR, content ≥99.6%, particle size 150-200 mesh, Jinan Zhiheng Zhiyuan Chemical Technology Co., Ltd.;
[0042] Emulsified paraffin: milky white liquid, density 0.9-1.0g / cm 3 , solid content ≥42%, Zhaoqing Lihe Technology Development Co., Ltd.;
[0043] Release agent, PAT-7399 / C, from Woss, Germany;
[0044] Wooden raw materials: surface layer and core layer materials, poplar, initial moisture content 12-15wt%, Wanhua Hexiang Board Industry (Huaiyuan) Co., Ltd.
[0045] Particleboard preparation steps:
[0046] Preparation of surface unit: Dry the surface raw material of particle board to a moisture content of 3%-5%, and put it into a closed drum glue mixer for stirring. Weigh 3.5wt% of the surface raw material mass of component (a) as an adhesive, and add component (a) evenly to the surface raw material in the form of air flow atomization (air pressure 0.3-0.5MPa); weigh a certain mass of component (b), dilute it with industrial water at a mass ratio of 1:3, and add it to the surface raw material in the form of air flow atomization; weigh a certain mass of component (c), dissolve it in 50℃ warm water, and add it to the surface raw material in the form of air flow atomization; add industrial water to adjust the moisture content of the surface wood particles to 13wt%-15wt%, and obtain the surface unit.
[0047] Preparation of core layer unit: Dry the core layer raw material to a moisture content of 2%-4%, put it into a closed drum mixer for stirring, weigh 3wt% of the core layer raw material mass of PMDI as an adhesive, and add it evenly to the core layer raw material in the form of air flow atomization (air pressure 0.3-0.5MPa); add industrial water to adjust the moisture content of the core layer shavings to 4wt%-6wt% to obtain the core layer unit.
[0048] Put the 50*50cm stainless steel metal pad into the hot press for preheating and spray the release agent. Use manual paving to pave the particleboard in the 35*35cm box mold. The particleboard has a three-layer structure of "surface-core-surface" and the paving quality ratio is 1:3:1. After paving, use a cold press for pre-pressing with a pre-pressing thickness of 50mm. After pre-pressing, hot pressing is performed with a thickness gauge of 18mm. The hot pressing process uses a three-stage pressure, which is divided into three stages: high, medium and low. The high pressure is set to 12MPa, the medium pressure is set to 8MPa, and the low pressure is set to 4.5MPa. The holding time ratio is 4:4:3, the hot pressing factor is 6s / mm, the total hot pressing time is 108s, and the hot pressing temperature is 220℃.
[0049] After hot pressing, the slabs are aged at room temperature for 2-3 hours to allow them to be fully cooled. After being stacked and stored for 3-5 days, the surfaces are sanded. After sanding, some of the slabs are sampled and tested for internal bonding strength (IB), surface bonding strength (SB), elastic modulus (MOE), static bending modulus (MOR), and 24-hour water absorption expansion rate (24h-TS) according to the national standard "GBT 17657-2013 Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels".
[0050] Comparative Example 1
[0051] The amount of PMDI added to the surface unit is 3.5% of the raw material weight, the amount of component (b) (EVA) is 15% of the amount of component (a) (PMDI), and (c) (p-aminobenzenesulfonamide) is not added; the other conditions are the same as the aforementioned "particleboard preparation steps". After the board is made, its performance is tested, and the test results are shown in Table 1.
[0052] Comparative Example 2
[0053] The amount of PMDI added in the surface unit is 3.5% of the weight of the raw materials, the amount of component (b) (EVA) is 30% of the amount of component (a) (PMDI), and component (c) (p-aminobenzenesulfonamide) is not added; the other conditions are the same as those in comparative example 1, and the performance of the board is tested after making. The test results are shown in Table 1.
[0054] Example 1
[0055] The particleboard was prepared by the aforementioned "particleboard preparation step". In the surface particle unit, the amount of component (b) (EVA) was 15% of the amount of component (a) (PMDI), and the amount of component (c) (p-aminobenzenesulfonamide) was 1% of the amount of component (a) (PMDI). After the board was prepared, its performance was tested, and the test results are shown in Table 1.
[0056] Example 2
[0057] The particleboard was prepared by the aforementioned "particleboard preparation step". In the surface particle unit, the amount of component (b) (EVA) was 15% of the amount of component (a) (PMDI), and the amount of component (c) (p-aminobenzenesulfonamide) was 5% of the amount of component (a) (PMDI); after the board was prepared, its performance was tested, and the test results are shown in Table 1.
[0058] Example 3
[0059] The particleboard was prepared by the aforementioned "particleboard preparation steps". In the surface particle unit, the amount of component (b) (EVA) was 30% of the amount of component (a) (PMDI), and the amount of component (c) (p-aminobenzenesulfonamide) was 5% of the amount of component (a) (PMDI). After the board was prepared, its performance was tested, and the test results are shown in Table 1.
[0060] Table 1 Test results of plates of comparative examples 1-2 and embodiments 1-3
[0061] IB / Mpa SB / Mpa MOE / Mpa MOR / Mpa 24h-TS / % Comparative Example 1 0.44 0.92 1790 13.38 15.53 Comparative Example 2 0.43 0.95 1779 13.68 16.75 Example 1 0.44 1.05 1811 14.87 5.11 Example 2 0.47 1.09 1867 14.11 5.64 Example 3 0.50 1.11 1876 15.56 5.77
[0062] It can be seen from Comparative Examples 1-2 that the addition of component (b) (EVA) does not improve the water resistance of the board and may even have a negative impact on the water resistance of the board. This is mainly because component (b) (EVA) is an aqueous emulsion and is more susceptible to water absorption.
[0063] Examples 1-3 are the test results of board making under normal PMDI addition. It can be seen from the table that using the components of the present invention to make boards can improve the waterproof performance of the boards to the greatest extent, making the boards meet the ultra-waterproof grade requirements.
[0064] Comparative Example 3
[0065] In Comparative Example 3, paraffin components are added to the surface layer and the core layer, and the added amount is 0.5% of the unit mass of the surface layer and the core layer respectively. The amounts of other components and the board making steps are the same as those in Comparative Example 1. The test results are shown in Table 2.
[0066] Comparative Example 4
[0067] In Comparative Example 4, paraffin components are added to the surface layer and the core layer, and the added amount is 1% of the unit mass of the surface layer and the core layer respectively. The amounts of other components and the board making steps are the same as those of Comparative Example 3. The test results are shown in Table 2.
[0068] Table 2 Comparative Example 3-4 Plate Test Results
[0069] IB / Mpa SB / Mpa MOE / Mpa MOR / Mpa 24h-TS / % Comparative Example 3 0.36 0.81 1562 12.11 12.80 Comparative Example 4 0.29 0.65 1327 10.87 9.15
[0070] It can be seen from Comparative Examples 3-4 that increasing the amount of paraffin wax can indeed improve the waterproofness of the board, but as the amount of paraffin wax added increases, the performance of the board is significantly reduced. This is mainly because the paraffin wax hinders the adhesion of the glue to the board. From a production analysis, adding paraffin wax also requires increased equipment investment.
[0071] Finally, it should be noted that the above embodiments are only used to describe the preferred implementation methods of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that various modifications and improvements made by modifying or equivalently replacing the technical solution of the present invention should fall within the protection scope determined by the claims of the present invention.
Claims
1. An isocyanate adhesive composition comprising the following components: (a) 100 parts by mass of polyfunctional isocyanate; (b) 3-50 parts by mass, preferably 15-30 parts by mass, of an aqueous emulsion; (c) Sulfonamide auxiliary agent: 1-20 parts by weight, preferably 1-5 parts by weight.
2. The composition according to claim 1, characterized in that The component (a) polyfunctional isocyanate is selected from one or more of aromatic polyisocyanates, aliphatic polyisocyanates, aromatic aliphatic polyisocyanates and alicyclic polyisocyanates, preferably aromatic polyisocyanates; more preferably one or more of toluene diisocyanate, diphenylmethane diisocyanate and polymethylene polyphenyl isocyanate.
3. The composition according to claim 1 or 2, characterized in that The aqueous emulsion of component (b) is selected from one or more of aqueous polyurethane, ethylene-vinyl acetate emulsion, polyvinyl acetate, polyvinyl alcohol, and aqueous acrylic emulsion, preferably ethylene-vinyl acetate emulsion.
4. The composition according to claim 3, characterized in that The waterborne polyurethane emulsion has a solid content of 45%-55%; the ethylene-vinyl acetate emulsion has a solid content of 45%-55% and a viscosity of 600-1500 cP.
5. The composition according to any one of claims 1 to 4, characterized in that The sulfonamide auxiliary agent is selected from one or more of sulfamide, methoxybenzenesulfonamide, p-toluenesulfonamide, chlorosulfonamide, arylsulfonamide, and p-aminobenzenesulfonamide, preferably p-aminobenzenesulfonamide.
6. A method for preparing a formaldehyde-free artificial board, comprising the following steps: (1) applying component (a), component (b) and component (c) to a surface layer raw material to prepare a surface layer unit; wherein: The components (a), (b) and (c) are the components in the composition according to any one of claims 1 to 5; Adding isocyanate to the core layer raw material to prepare a core layer unit; (2) The moisture content of the surface layer unit and the core layer unit obtained in step (1) is adjusted, and then a process including paving, pre-pressing and hot pressing is performed to obtain a formaldehyde-free artificial board rough board.
7. The method according to claim 6, characterized in that During the preparation of the surface layer unit, the amount of component (a) is 2 wt% to 10 wt%, preferably 3 wt% to 3.5 wt%, of the surface layer raw material.
8. The method according to claim 6, characterized in that In the preparation process of the core layer unit, the isocyanate is selected from aromatic polyisocyanates, aliphatic polyisocyanates, aromatic aliphatic polyisocyanates and alicyclic polyisocyanates, preferably toluene diisocyanate, diphenylmethane diisocyanate and polymerized diphenylmethane diisocyanate, more preferably PMDI; more preferably, the amount of isocyanate used is 2wt% to 10wt% of the core layer raw material, preferably 3wt% to 3.5wt%.
9. The method according to any one of claims 6 to 8, characterized in that: The surface layer and core layer raw materials include at least one of wood crushed material, bamboo crushed material, straw crushed material, and cotton and linen stalk raw materials, and the moisture content is preferably 2-6%; among them, preferably, the moisture content of the surface layer raw material is 3%-5%, and the moisture content of the core layer raw material is 2%-4%.
10. The method according to any one of claims 6 to 9, characterized in that: In step (2), the moisture content of the surface layer unit is adjusted to 13wt%-15wt%, and the moisture content of the core layer unit is adjusted to 4wt%-6wt%.
Citation Information
Cited By
Bio-based polyurethane resin, preparation method thereof and bio-based high-moisture-permeability waterproof membrane
CN120718239A
